2008
DOI: 10.1029/2007jd009491
|View full text |Cite
|
Sign up to set email alerts
|

Importance of anthropogenic inputs and continental‐derived dust for the distribution and flux of water‐soluble nitrogen and phosphorus species in aerosol within the atmosphere over the East China Sea

Abstract: [1] We analyzed 156 aerosol samples, including 10 dust storm samples, collected from January to December 2005 at a coastal site on the southern East China Sea at Keelung city, Taiwan, for water-soluble major ions, nitrogen, and phosphorus species. In addition, 4-d back trajectories of air masses arriving daily at the sampling site were calculated to determine the potential aerosol source regions. The obtained concentrations of major ions indicate that a continental source was dominant from January to May and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 61 publications
1
46
1
Order By: Relevance
“…Although some rain samples had basic pH values up to 8.8, indicating some neutralization of acids, possibly from dust-based CaCO 3 [Nenes et al, 2011], no relationship was observed between pH and SRP or dust. These findings are in contrast to several studies that found good correlations (in aerosols) between SRP and nss-SO 4 2À and -Ca 2+ in east China [Chen and Chen, 2008] and between SRP and nss-Ca 2+ in the Bay of Bengal [Srinivas and Sarin, 2012]. A lack of strong correlations with different source indicators in rain indicates that there was no predominant source of SRP in Miami or that rain P sources are relatively complex compared with those in eastern China, where anthropogenic aerosol concentrations are in general very high and intense pollution events very frequent.…”
Section: Phosphorus In Raincontrasting
confidence: 55%
See 2 more Smart Citations
“…Although some rain samples had basic pH values up to 8.8, indicating some neutralization of acids, possibly from dust-based CaCO 3 [Nenes et al, 2011], no relationship was observed between pH and SRP or dust. These findings are in contrast to several studies that found good correlations (in aerosols) between SRP and nss-SO 4 2À and -Ca 2+ in east China [Chen and Chen, 2008] and between SRP and nss-Ca 2+ in the Bay of Bengal [Srinivas and Sarin, 2012]. A lack of strong correlations with different source indicators in rain indicates that there was no predominant source of SRP in Miami or that rain P sources are relatively complex compared with those in eastern China, where anthropogenic aerosol concentrations are in general very high and intense pollution events very frequent.…”
Section: Phosphorus In Raincontrasting
confidence: 55%
“…However, Miami yielded higher N/P wet deposition ratios than Barbados because of higher N concentrations associated with the more frequent impact of terrestrial/polluted air masses. Higher N/P ratios in polluted areas have been previously predicted and observed [Chen and Chen, 2008;Mahowald et al, 2008].…”
Section: P and N Dry Depositionmentioning
confidence: 87%
See 1 more Smart Citation
“…As a result, the atmospheric deposition of iron is seen to be the most important factor in phytoplankton growth in the ECS; nitrogen also plays an important part, whereas phosphorus has less impact. Previous studies have indicated that atmospheric phosphorus may not be a vital source of inorganic phosphorus in the ECS [62,67].…”
Section: Simulated Dust Deposition Estimations Of Nutrients and Theimentioning
confidence: 99%
“…Soluble phosphorus (10.3 µg·m −2 ·d −1 ) was more than three times higher than the mean value of 3.3 µg·m −2 ·d −1 derived by Hsu et al [62] from dry deposition in the northeasterly monsoon period. The amount of soluble phosphorus of 10.3 µg·m −2 ·d −1 corresponds to 0.95 mg·m −2 in spring 2010, which accounts for 63% of the yearly dry deposition of dissolved inorganic phosphorus from dust storm samples (1.5 mg·m −2 ) obtained by Chen and Chen [67]. The total estimated deposition of total inorganic nitrogen supported by a mean dust deposition flux of 64.7 mg·m −2 ·d −1 was 0.6 mg·m −2 ·d −1 , which was comparable with the mean value of 0.69 mg·m −2 ·d −1 previously derived from dry deposition over the ECS [62].…”
Section: Simulated Dust Deposition Estimations Of Nutrients and Theimentioning
confidence: 99%